Factors influencing personalization of dwellings among residents of selected public housing estates Lagos Nigeria (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Several factors have been implicated as responsible for personalization of dwellings. These factors ranges from demographic, socioeconomic and cultural. Demographic factors however, have been most frequently cited with respect to housing behaviour of households. Within the context of public housing, this study seeks to investigate factors influencing personalization of dwellings among residents of public housing estates using selected Public Housing Estates of the Lagos State Development and Property Corporation (LSDPC) as case study. The cross-sectional survey research design was employed in this study. This involved collection of primary data using structured questionnaire and personal observations. Four public housing estates were selected purposively comprising three low-income and one medium-income housing estate out of 22 low-income and 10 medium-income estates, being the largest estates. The sampling frame for the four selected estates comprised 9734 housing units in 1361 blocks of flat out of which systematic random sampling was used to select a sample size of 973 housing units.The result of the binary logistic regression revealed gender, religion, educational and income level, current household size, satisfaction with housing design, living status and availability of alternative dwelling were all significantly associated with personalization of dwellings. Lower odds of personalization was found among the men (OR=0.003, p
Keywords: Dwellings; Lagos Nigeria; Personalization of dwellings; Public housing